Kelas Tertutup Konjungsi pada Antologi Puisi Sebatas Angan Rindu Karya Fina Af’idatussofa dan Upik Lestari - Ila Nafilah; Reni Rokhayati; Yulia Agustin (Pusat Riset dan Inovasi Nasional, 2023)
Morphology is a field of linguistics that studies morphemes and their combinations. Morphological objects are things related to word forms or word structures in language. In the study of morphology, there is a closed class and open class word classification. One of the closed class word classifications is conjunctions. Conjunctions are used to connect two or more clauses, both of which have a syntactic structure or have a different syntactic structure. The types of conjunctions include: coordinating conjunctions, subordinating conjunctions, and conjunctions between sentences. The choice of topics in this study was based on the finding of closed conjunction classes in the poetry anthology Sebatas Angan Rindu by Fina Af'idatussofa and Upik Lestari. The purpose of this research is to analyze and obtain a clear picture of closed classes of conjunctions, such as coordinating conjunctions, subordinating conjunctions, and conjunctions between sentences contained in the poetry anthology Sebatas Angan Rindu by Fina Af'idatussofa and Upik Lestari. This study used descriptive qualitative method. The data source used is the poetry anthology Sebatas Angan Rindu by Fina Af'idatussofa and Upik Lestari published by the QT Millennials Library in 2006 which can be accessed via the link https://aseranikurdi.files.wordpress.com/2011/09/antologi-puisi-sebatas-angan-rindu.pdf. The sub-focus in this study is the closed class of conjunctions consisting of coordinating conjunctions, subordinating conjunctions, and conjunctions between sentences. Keywords: Morphology, closed class conjunctions and poetry